2014
DOI: 10.1021/es404988k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manure Application on Abundance of Antibiotic Resistance Genes and Their Attenuation Rates in Soil: Field-Scale Mass Balance Approach

Abstract: The development of models for understanding antibiotic resistance gene (ARG) persistence and transport is a critical next step toward informing mitigation strategies to prevent the spread of antibiotic resistance in the environment. A field study was performed that used a mass balance approach to gain insight into the transport and dissipation of ARGs following land application of manure. Soil from a small drainage plot including a manure application site, an unmanured control site, and an adjacent stream and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 40 publications
11
112
0
1
Order By: Relevance
“…The drought conditions in the summer of 2012 in Northeast Iowa may have caused additional stress to bacteria hosting the resistance genes and therefore hastened the return of overall concentrations to those found in no-manure control plot soils (Cools et al, 2001;Byappanahalli et al, 2012). The reduction in ermB and ermF genes in soil over winter are similar to those reported previously (Garder et al, 2014;Fahrenfeld et al, 2014). Enterococci concentrations in tile drainage were not significantly different (p N 0.10) across tillage or manure treatments.…”
Section: Discussionsupporting
confidence: 72%
“…The drought conditions in the summer of 2012 in Northeast Iowa may have caused additional stress to bacteria hosting the resistance genes and therefore hastened the return of overall concentrations to those found in no-manure control plot soils (Cools et al, 2001;Byappanahalli et al, 2012). The reduction in ermB and ermF genes in soil over winter are similar to those reported previously (Garder et al, 2014;Fahrenfeld et al, 2014). Enterococci concentrations in tile drainage were not significantly different (p N 0.10) across tillage or manure treatments.…”
Section: Discussionsupporting
confidence: 72%
“…Although chemical fertilizer had some effects on soil ARGs, these effects, not surprisingly, are weaker when compared with sewage sludge or chicken manure, considering that manure is rich in ARGs and ARBs , Jiang et al, 2002Ghosh and LaPara, 2007) and most ARGs are discharged from the municipal wastewater treatment process in the form of sewage sludge (Munir et al, 2011). However, land application of animal manure or sewage sludge does not universally increase ARGs in soils (Zhou et al, 2010) and this increase is not maintained long-term (Fahrenfeld et al, 2014). For instance, manure from three dairy farms did not increase cultivable chlortetracycline-resistant bacteria when land-applied to soil (Ghosh and LaPara, 2007).…”
Section: Responses Of Args Abundance and Compositionmentioning
confidence: 99%
“…Marti et al (2014) indicated that genes of sul1, ermB, strB, intI1 and IncW repA increased significantly in the week following application and then declined, but the ermB could not decline to background level after 1 year period with application of swine manure. Fahrenfeld et al (2014) reported that ermF, sul1 and sul2 dissipated to background levels within 2 months following (2014) a Antibiotic resistance mechanism is categorized according to Blair et al (2014); ribosomal protection protein genes of tetracycline, modified dihydropteroate synthase enzyme genes, and 23S rRNA methyltransferase genes are classified into target site protection mechanism. b [ represents increased and Y represents decreased after anaerobic digestion.…”
Section: Args In Soil Of Farmmentioning
confidence: 99%